Taxonomic review of the genus Peltogyne Vogel (Leguminosae, Detarioideae) - Kochanovski, Fabio J.; Nogueira, Luan H.p.; Rosa, Marcus P.g.; Mansano, Vidal F.; Sartori, Ângela L.b. (Phytotaxa, 2025)
We present the taxonomic revision of the genus Peltogyne with an identification key, descriptions, illustrations, and taxonomic comments for each species. Specimens from 22 herbaria, including scanned images, were evaluated, and collections and field observations were carried out. The species can be distinguished by the type of indumentum and shape of the leaflets and the indumentum of the ovary. Peltogyne has 25 species, including the recently described P. barbata. Lectotypifications were performed for P. altissima, P. confertiflora, and P. densiflora. Peltogyne prancei and P. crenulata were synonymized with Peltogyne heterophylla and Peltogyne pauciflora, respectively, and P. densiflora is being raised to the species rank. Peltogyne occurs from Mexico to Southeast Brazil. The species are widely distributed, mainly in the Atlantic Forest, Amazon Forest, and Caatinga. The following species have a restricted distribution: P. barbata is restricted to the Amazon region; P. discolor to the Atlantic Forest; P. gracilipes to Maracá Island and surroundings, Roraima; and P. maranhensis to the Caatinga. Updated geographic distribution data were essential for a better circumscription of the species and made it possible to understand their areas of occurrence.